한국인 연령관련황반변성환자의 사회적 비용 분석 - 안용선(Yongsun Ahn), 지동현(Donghyun Jee) (Daihan angwa haghoi jabji, 2019)
목적: 사회적 관점에서 국내 연령관련황반변성환자의 연간 질병비용을 추정하고자 한다. 대상과 방법: 사회적 관점에서 질병비용 분석을 시행하였으며, 비용항목으로 의료비용, 비의료비용 그리고 생산성 손실비용을 분석하였다. 의료비용은 공식적 의료비용과 비공식적 의료비용으로 세분하였으며, 비의료비용은 교통비용, 시간비용, 간병비용으로 세분하였다. 자료원으로는 국민건강보험공단 청구자료, 국민건강보험공단 표본 코호트 자료, 한국의료패널 등을 이용하였다. 결과: 2016년 국내 연령관련황반변성환자의 사회적 비용은 약 6,943억 원으로 추정되었다. 이 중 의료비용은 약 5,009억 원(72.1%), 비의료비용은 약 609억 원(8.8%), 그리고 생산성 손실비용은 약 1,325억 원(19.1%)이었다. 연령관련황반변성환자 1인당 평균 사회적비용은 약 1,323,980원이었다. 결론: 본 연구를 통해 연령관련황반변성의 사회적 비용 규모와 그 내용을 파악할 수 있었다. 특히 생산성 손실비용이 약 20%를 차지하였다는 것은 연령관련황반변성이 노동력 상실에 미치는 영향이 크다는 것을 시사한다. 국내에도 고령화 사회가 도래함에 따라 향후 연령관련황반변성의 질병비용이 지속적으로 늘어날 것으로 예상되므로, 국가적으로 사회경제적 비용 절감을 위해 연령관련황반변성의 치료와 예방에 대한 적극적인 방안이 필요할 것으로 사료된다. Purpose: To estimate the annual socioeconomic costs of age-related macular degeneration (AMD) in the Republic of Korea. Methods: We estimated the costs of illness to society of AMD patients, including medical, nonmedical, and productivity costs. The medical costs included official and nonofficial medical costs, and the nonmedical costs consisted of transportation, time, and nursing costs. We used Korea National Health Insurance Claims Database, National Health Insurance Service-National Sample Cohort, and Korea Health Panel study data in the analysis. Results: The socioeconomic costs of AMD were estimated to be 694 billion Korean won (KRW) in 2016. This figure was divided into 501 billion KRW (72.1%) for medical costs, 61 billion KRW (8.8%) for nonmedical costs, and 133 billion KRW (19.1%) for productivity costs. The annual per capita socioeconomic cost of AMD was 1.32 million KRW. Conclusions: We determined the scale and composition of the socioeconomic costs of AMD. Importantly, the productivity costs accounted for approximately 20% of all costs, suggesting that AMD had a significant impact on productivity. Because the disease costs of AMD are expected to increase continuously with the aging population, effective planning at the governmental level for prevention and treatment of AMD should be considered to reduce socioeconomic costs. KCI Citation Count: 1